การจำลองการไหลในน้ำตื้นที่มีพจน์แหล่งต้นทาง - ศศิเกษม สัทธรรมสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
When the horizontal scale of fluid flow is large comparing to vertical scale, the flow can generally be approximated as shallow water problem governed by the so-called shallow water equations (SWE). SWE has been widely used to model various problems such as flood wave, dam-break problem, open-channel flows and many others. The topic of dam-break problem has increasingly attracted attention of mathematicians, engineers and physicists in the fields of environmental protection, flood plain analysis and water resource management. A theoretical model of these problems represents not only the real dam break situation but also a sudden change of water level caused by flash flood or heavy rainfall in a small time period. Among various well established numerical methods for finding its solution, finite volume approach appear to have more popularity in the research community. This is due to its applicability to handle the hyperbolicity nature of homogenous SWE which admits discontinuities in the system solutions. However, when the source term, e.g., bed slope and bottom friction is included in the SWE there is still a question of how to appropriately incorporate this term in the numerical treatment. In an attempt to explore difficulties present in the existing numerical models, a two-dimensional finite volume method for SWE with source term is proposed to solve conservation system of dam-break problem based on the upwind Godunov ‘s method.